Character Migration: the Case of Sherlock Holmes - Nicholas TUCKER (E-REA)
Sir Arthur Conan Doyle’s famous character Sherlock Holmes continues to re-appear in novels right up to our own day. Some of these authors in the course of their stories also try to explain Holmes’s eccentric psychology at the same time. Others concentrate on introducing those modern social sensibilities felt to be lacking in some of the original stories. A third group speculates what might have happened to Holmes in old age while a fourth takes the opportunity to criticise both Holmes and his methods. Each approach tells us much about the authors involved and their own values. But do any of their stories actually advance our understanding of Sherlock Holmes himself?